CHARACTERISTICS OF EDIBLE FILM MADE FROM PECTIN FROM BALI ORANGE PEEL WITH THE ADDITION OF BEESWAX and CHITOSAN - Muryeti, Muryeti (Jurnal Chemurgy, 2026)
The use of conventional plastic as packaging causes environmental problems because it is difficult to decompose. One environmentally friendly alternative is edible film based on natural biopolymers. This study used pectin from grapefruit peel with the addition of glycerol as a plasticiser, as well as a combination of chitosan (0–2%) and beeswax (0–3%) to improve the functional properties of the film. The edible film was produced using a 3x4 factorial Complete Randomised Design (CRD) method, then tested for its physical, mechanical, and biodegradable properties. The results showed that an increase in beeswax concentration reduced the film's transparency, tensile strength, solubility, and biodegradability, but increased its hydrophobicity and flexibility. Chitosan played a role in strengthening the structure and adding antimicrobial properties, but reduced elasticity. ANOVA analysis showed that chitosan and beeswax, both individually and in combination, had a significant effect on most of the test parameters. Thus, the combination of pectin, chitosan, and beeswax can produce edible films with properties that can be adjusted for sustainable food packaging applications.